2022
DOI: 10.1007/s11064-022-03532-0
|View full text |Cite
|
Sign up to set email alerts
|

DHI Increases the Proliferation and Migration of Schwann Cells Through the PI3K/AKT Pathway and the Expression of CXCL12 and GDNF to Promote Facial Nerve Function Repair

Abstract: BackgroundDanhong injection (DHI) is a commonly used drug in the treatment of cardiovascular and cerebrovascular diseases, and its neuroprotective research has been fully con rmed. Schwann cells, as myelin forming cells of peripheral nerve, play an important role in the process of injury and repair. The purpose of this study was to explore the effect of DHI on Schwann cells and its role in facial nerve injury. MethodsRSC 96 Schwann cells were treated with different concentrations (0 -2%) of DHI for different t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Gao et al found that activating the PI3K/Akt pathway boosted SC proliferation, aiding remyelination and nerve regeneration post-facial nerve injury. [70] Ma et al found that the proliferative capability of SCs was restored by downregulating the long non-coding RNA, which negatively affected the PI3K/Akt pathway, subsequently facilitating functional recovery in rats post sciatic nerve injury. [71] Therefore, it can be inferred that PPSB 60:40 nanofibers enhanced SC proliferation by activating the PI3K/Akt signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Gao et al found that activating the PI3K/Akt pathway boosted SC proliferation, aiding remyelination and nerve regeneration post-facial nerve injury. [70] Ma et al found that the proliferative capability of SCs was restored by downregulating the long non-coding RNA, which negatively affected the PI3K/Akt pathway, subsequently facilitating functional recovery in rats post sciatic nerve injury. [71] Therefore, it can be inferred that PPSB 60:40 nanofibers enhanced SC proliferation by activating the PI3K/Akt signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The endogenous nervous system consists of intestinal neurons and intestinal glial cells, of which the latter can maintain the integrity of the enteric nervous system and secrete glial cell-derived neurotrophic factor (GDNF), a nutritional factor that promotes neuronal growth, differentiation, and repair (6). The PI3K/AKT axis involved in GDNF has also been shown to work in the maintenance and differentiation of NSCs in the developing brain and contributes to the recovery of neurological function after CI injury (7,8). However, it remains to characterize whether NSC transplantation plays a role in treating ischemic brain injury through the GDNF/PI3K/AKT axis.…”
Section: Introductionmentioning
confidence: 99%